Pengaruh Profitabilitas, Ukuran Perusahaan, Kualitas Audit, dan Komite Audit terhadap Penghindaran Pajak : Studi Empiris pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2019 - 2023 - Anisya Rizki Hadiati; Roza Fitria (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the influence of profitability, company size, audit quality and audit committee on Tax Avoidance in property and real estate companies listed on the Indonesian Stock Exchange in 2019 - 2023, as many as 94 companies. The sampling technique used was the purposive sampling method and 220 sample data were obtained from 44 companies. The analysis technique used in this research is a multiple linear regression analysis test using the Statistical Package for the Social Sciences (SPSS) program. The population in this research is Property and Real Estate companies listed on the Indonesian Stock Exchange. The results of this research show that Profitability Committee has a positive and significant effect on Tax Avoidance, while Company Size, Audit Quality and Audit Committee have no effect on Tax Avoidance.